2013
DOI: 10.1002/9781119421450
|View full text |Cite
|
Sign up to set email alerts
|

Dentist's Guide to Medical Conditions, Medications, and Complications

Abstract: 1427rotations in our medical radiology department and in the three years of their program.Since the book is rather expensive (like all good radiology books, due the cost of high-quality paper and proper image management), it is hard to recommend it for personal purchase; however, a group practice may find the price reasonable. I would definitely recommend the book for a communal library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Secondly, that previous study's hypothesis and interpretations did not take into account whether human bone responds to biomechanical loading in the same way as soft tissue. Previous research has shown that new bone formation as a response to biomechanical stress and bone remodeling is typically complete after approximately four to 8 months on average (Ganda, ), while there are experimental cases in which the levels of bone formation (based on biochemical markers) in adult athletes remained relatively constant over 12 months of systematic training (e.g., Bennell et al, ; Maimoun and Sultan, ). It should be emphasized that this process can be even slower for bone in fibrocartilaginous entheses, as these comprise gradients reducing stress concentration by dissipating it across the entire attachment area (Benjamin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, that previous study's hypothesis and interpretations did not take into account whether human bone responds to biomechanical loading in the same way as soft tissue. Previous research has shown that new bone formation as a response to biomechanical stress and bone remodeling is typically complete after approximately four to 8 months on average (Ganda, ), while there are experimental cases in which the levels of bone formation (based on biochemical markers) in adult athletes remained relatively constant over 12 months of systematic training (e.g., Bennell et al, ; Maimoun and Sultan, ). It should be emphasized that this process can be even slower for bone in fibrocartilaginous entheses, as these comprise gradients reducing stress concentration by dissipating it across the entire attachment area (Benjamin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal drug therapy is achieved by combining drugs with complementary mechanisms of action with the aim of reducing postoperative pain (Brooks et al, 2017; Matute Crespo and Montero Matamala, 2017). When treating moderate to severe pain, combination pharmacotherapy may be an effective alternative to treat pain and improve patient recovery times (Ganda, 2008). Originally, multimodal analgesia was advocated for use in ambulatory anesthesia combining NSAIDs and opioid analgesics, with or without anesthetic infiltration (Devin and McGirt, 2015).…”
Section: Current Pharmacological Approaches For Dental Pain Treatmentmentioning
confidence: 99%
“…Amoksisilin memiliki spektrum yang mirip dengan ampisilin namun kerja antibiotik ini lebih aktif jika dibanding dengan ampisilin. Penambahan asam klavulanat ke amoksisilin memperluas atau memulihkan spektrum amoksisilin (Ganda, 2013;Haveles, 2016;Starlin & Richard, 2005).…”
Section: Pola Sensitivitas Bakteri Terhadap Antibiotikunclassified